O processo de gestão da educação no sistema municipal de ensino de Soledade: uma experiência de democracia de alta intensidade - Azambuja, Ádria Brum de (2020)
The management of education and the democratization of school management have been the nucleus of studies and research in different contexts. There are multiple experiences that reveal the constitution of educational policies that reaffirm the commitment to democracy. In the municipality of Soledade / RS, educational actions mobilize a management project based on participatory democracy. In this dissertation, the general objective is to reflect on the democratic management process in motion in the Municipal Education System of Soledade / RS, deepening the implications of high intensity democracy according to Boaventura de Sousa Santos. The work constitutes a case study anchored in the interpretive and critical paradigm, in bibliographic, documentary research and participant observation. Triangulating the collective project, the practices developed and the theoretical contributions, it will be possible to enhance the core of the research considering the following specific objectives: a) to deepen the principles that underpin a democratic management of participatory education in the SME; b) to diagnose advances, resistances and tensions related to the high-intensity democracy process that involve multiple subjects with plural pedagogical and political horizons. The present study is organized in five chapters including the introduction and the final considerations. Initially, I present elements of the socio-historical and cultural context of the municipality as the locus of work, as well as the founding nuclei that constitute the process of democratic management in the municipal system. In the third chapter, I dialectically socialize the actions developed in educational management, constituting the principles and foundations of participatory management. The fourth chapter describes the pedagogical work carried out at the Municipal Secretariat for Education, Culture and Sport - SMECD, signaling advances, resistances and tensions born in the context of high-intensity democracy. The local experience around the democratic management process, in movement, has been revealing the how much it is possible to collectively constitute projects that aim at citizen formation and reaffirm the belief in a more just and egalitarian world. The research reaffirms that high-intensity democracy, in the context of the hegemony imposed by capitalism, is entangled in advances and resistance, signaling that its materialization is directly associated with the political decision of the manager, the process of self-training of the subjects and the action / reflection on educational practices. Thus, it reiterates the thesis that participating is a political act of emancipation, imperative for the formation of democratic citizens.